Free-leg side elevation of pelvis in single-leg jump is a substantial advantage over double-leg jump for jumping height generation - Sado, N.; Yoshioka, S.; Fukashiro, S. (Journal of Biomechanics, 2020)
In single-leg jumps, humans achieve more than half the jumping height that they can reach for double-leg jumps. Although this bilateral deficit in jumping has been believed to be due to the reduction of leg extensor force/work exertions, we hypothesised that the three-dimensional biomechanical differences between double-leg and single-leg jumps also influence the bilateral deficit in jumping. Here, we show the substantial effect of the elevation of the pelvic free-leg side in single-leg squat jumps on the bilateral deficit in jumping in addition to extensor force reduction. We collected the kinematic and ground reaction force data during single-leg and double-leg squat jumps from ten male participants using motion capture systems and force platforms. We determined the components of the mechanical energy directly contributing to the height of the centre of mass due to segment movement. The energy due to rotations of the foot, shank, thigh, and pelvis were significantly greater in single-leg squat jumps than in double-leg squat jumps. The magnitudes of the difference in energy between single-leg and double-leg squat jumps due to the pelvis (0.54 ± 0.22 J/kg) was significantly larger than that due to any other segment (<0.30 J/kg). This indicates that pelvic elevation in single-leg jump is a critical factor causing bilateral deficit in jumping, and that humans generate the jumping height with a single leg not just by an explosive leg-extension but also by synchronous free-leg side elevation of the pelvis. The findings suggest that this pelvic mechanism is a factor characterising human single-leg jumps.